2014
DOI: 10.1155/2014/485620
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry and Multiplex Antigen Assays to Assess Microbial Quality and Toxin Production of Staphylococcus aureus Strains Isolated from Clinical and Food Samples

Abstract: The aim of our study was to investigate the microbial quality of meat products and on some clinical samples in Abidjan focused on Staphylococcus genus and the toxin production profile of Staphylococcus aureus (S. aureus) isolated. Bacteria were collected from 240 samples of three meat products sold in Abidjan and 180 samples issued from clinical infections. The strains were identified by both microbiological and MALDI-TOF-MS methods. The susceptibility to antibiotics was determined by the disc diffusion metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Indeed, the presence of methicillin-resistant strains in foods was reported in Germany by van den Broek (2003). The detection of resistant Staphylococcus in this study is of concern for food safety as this genus encompasses pathogenic species and in particular Staphylococcus aureus which can be resistant to antibiotics such as oxacillin and can produce toxin (Baba-Moussa et al, 2011, Attien et al, 2014. In 2010, an EFSA study at Abidjan reported similar results by showing that the main reservoir of methicillin-resistant Staphylococcus are pigs, calves and broilers (EFSA, 2010).…”
Section: Municipalitiesmentioning
confidence: 69%
“…Indeed, the presence of methicillin-resistant strains in foods was reported in Germany by van den Broek (2003). The detection of resistant Staphylococcus in this study is of concern for food safety as this genus encompasses pathogenic species and in particular Staphylococcus aureus which can be resistant to antibiotics such as oxacillin and can produce toxin (Baba-Moussa et al, 2011, Attien et al, 2014. In 2010, an EFSA study at Abidjan reported similar results by showing that the main reservoir of methicillin-resistant Staphylococcus are pigs, calves and broilers (EFSA, 2010).…”
Section: Municipalitiesmentioning
confidence: 69%
“…The resulting recombinant protein (rSEC epi ) was expressed and purified by affinity chromatography and the identity of the protein is confirmed by Western blot method as a ~27 kDa protein using rabbit affinity-purified S. aureus anti-enterotoxin C antibodies ( Figure 4 B) [ 28 ]. SEs are well-known to resist heating and digestive enzymes [ 28 , 29 , 30 ]. rSEC epi was able to keep 30% function after heating at 100 °C for 1 h as SEC aureus does ( Figure 5 and Figure 6 ), more or less, but it was less resistant than SEA, which resists beyond 8 h of heat treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of antibiotic-resistant strains between livestock and humans working with and/or consuming the former is a real problem, poorly understood to date ( 28 31 ). Furthermore, aerosol transmission of MRSA from farm animals or human patients in hospital wards, to humans, is also a scary reality ( 32 34 ).…”
Section: The Bacterium: Staphylococcus Aureusmentioning
confidence: 99%